2017
DOI: 10.1542/peds.2016-2364
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Variations in Unexpected Complications Among Term Newborns

Abstract: Variation in unexpected complication rates is more likely to be related to hospital rather than patient characteristics in Florida. The high proportion of variation explained by hospital factors suggests potential opportunities for improvement, and identifying specific complication categories may provide focus areas. Some of the opportunities may be related to differences in hospital coding practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
4
17
0
Order By: Relevance
“… 2 Guidelines for levels of maternal care and for obstetric analgesia and anesthesia published by the American College of Obstetricians and Gynecologists (ACOG) state that anesthesia services should be available to provide labor analgesia in all hospitals that offer maternal care. 3 , 4 Although geographical variability has been shown for obstetric procedures, such as abortion availability, 5 labor induction, 6 cesarean delivery, 7 and perinatal outcomes, 8 , 9 there is insufficient research to determine whether geographical variation exists across US states in neuraxial analgesia use. Therefore, documenting and understanding geographical variability in the use of neuraxial analgesia are essential undertakings to improve the quality of obstetric anesthesia care.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Guidelines for levels of maternal care and for obstetric analgesia and anesthesia published by the American College of Obstetricians and Gynecologists (ACOG) state that anesthesia services should be available to provide labor analgesia in all hospitals that offer maternal care. 3 , 4 Although geographical variability has been shown for obstetric procedures, such as abortion availability, 5 labor induction, 6 cesarean delivery, 7 and perinatal outcomes, 8 , 9 there is insufficient research to determine whether geographical variation exists across US states in neuraxial analgesia use. Therefore, documenting and understanding geographical variability in the use of neuraxial analgesia are essential undertakings to improve the quality of obstetric anesthesia care.…”
Section: Introductionmentioning
confidence: 99%
“…Our algorithm identified 2037 references of which 17 included composite indicators corresponding to our eligibility criteria . For 5 of the 17 indicators, we included the original article or other sources which described the construction of the indicator, instead of the article from our search . The flow chart of the selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Sebastiao et al 3 help to fill the knowledge gap about the care received by this understudied group of infants. Using data from 124 Florida hospitals with >100 deliveries annually, they found that "unexpected complications" after delivery were not unusual, with a rate of 37 complications per 1000 deliveries.…”
mentioning
confidence: 93%
“…The measure used in the study of Sebastiao et al 3 is a composite measure of unexpected newborn complications developed by the California Maternal Quality Care Collaborative. Composite measures are a useful method of combining potential measures of quality that occur rarely into more stable and reliable metrics.…”
mentioning
confidence: 99%